Ferroelectric properties of mechanically synthesized nanosized barium titanate - Stojanovic, B. D.; Jovalekic, C.; Vukotic, V; Simoes, A. Z.; Varela, José Arana [UNESP] (Taylor & Francis Ltd, 2005)
Barium titanate ceramics were prepared through mechanochemical synthesis starting from fresh prepared barium oxide and titanium oxide in rutile form. Mixture of oxides was milled in zirconia oxide jar in the planetary ball-mill during 30, 60, 120 and 240 min. Extended time of milling directed to formation of higher amount of barium titanate perovskite phase. Barium titanate with good crystallinity was formed after 240 min. Sintering without pre-calcinations step was performed at 1330 degrees C for 2 hours with heating rate of 10 degrees C/min. The XRD, DSC, IR and TEM analyses were performed. Electric and ferroelectric properties were studied. Very well defined hysteresis loop was obtained.
Keywords: mechanochemical synthesis; dielectric properties; ferroelectric properties; barium titanate